Penerapan Metode Six Sigma (DMAIC)Untuk Menuju Zero Defect Pada Produk Air Minum Ayia Cup 240 ml - Meldia Ananda; Gamindra Jauhari; Surga Ridwani (Universitas Katolik Musi Charitas, 2019)
Company can be competitive in industry by providing a good quality product according to specification and have no defect. Used DMAIC concept (Define, Measure, Analyze, Improve, Control) of six sigma method can be used to get zero defect level. The defines phase used to identify the problem. The measures phase used performed to measure the level of disability in a production. The analyzes phase to determine the cause of problem in production process using fishbone diagram. Improvements phase used to improve the process and eliminate the cause of disability based on the analyze phase. The last phase is the controls phase, used to control the performance and ensure the main problems cause the disability does not reappear using Statistical Process Control (SPC). From the result of analysis data obtained DPMO value and sigma level before the application of six sigma method is 30,020 cups per million production on 3.38 sigma level. Whereas after the application of six sigma method obtaining DPMO 7,093 cups per million production on 3.95 sigma level. With the result, reduction of defect is as much as 22,927 cups.